Legal Protection on Apartment Units’ Customers with PPJB When the Developer is Failed - Hanafi Hanafi; Eriyantouw Wahid; Gunawan Djajaputra (Indonesian Journal of Multidisciplinary Science, 2022)
The purpose of this study is to find out the legal protection regulations for buyers, the efforts that buyers of apartment units can take in the form of PPJB if the developer is declared bankrupt and how the law should give rights to the apartment buyers. Research on the above problems was conducted using qualitative methods. The type of research used is normative empirical by using approaches with methods of legal interpretation, legal construction, legal philosophy, legal history, and comparative law, as well as a legal pluralism approach. The data used in this dissertation research are primary and secondary and tertiary data which are analyzed objectively based on existing juridical references in order to obtain answers to the problems. Based on the research results from the problems above, it is concluded that there are several arrangements regarding the protection of buyers/consumers in Indonesian positive law, both from civil law, criminal law, customary law, and Islamic law. Buyers of apartment units can also sue in accordance with Article 3 of the UUK and PKPU, although the process must take a long time. The law should provide an update by adding a clause in the PPJB that objects being traded cannot be included in the bankruptcy budget.